Firm-Level Early Intervention Incentives: Which Recent Employers of Disability Program Entrants Would Pay More?. (December 2017) - Stapleton, David C.; Mann, David R.; Singh, Pragya; Song, Jae
The declining economic status of people with disabilities and the predicted 2016 depletion of the Social Security Disability Insurance (DI) Trust Fund have generated considerable interest in proposals for reforming the DI program. Some proposals would hold firms partially responsible for a portion of the DI benefits paid to their recent employees. We analyze the implications of this approach for employers and workers in general, and specifically consider two prominent reform proposals: One would require employers to carry short-term DI; the second would apply an experience rating to the DI portion of the Federal Insurance Contributions Act premium. We find the proposals would place a relatively large burden on the labor costs of many relatively small (fewer than 500 workers), low-wage firms. Firms with high potential liabilities might react by seeking to accommodate and retain workers with challenging medical conditions but might also reduce hiring or retaining workers at high risk of medical problems. Hence, although these proposals would likely reduce DI expenditures, they might have less desirable unintended consequences.